Coping with psychological impact of disasters through physical education and sports among children living in disaster-prone areas (2017)
The focus of this paper was to explain the concept of disaster, its impacts on sports and recreation facilities and how disasters can be prevented in schools. It also addressed how to cope with psychological impact of disasters among children through physical education and sports